Development and psychometric appraisal of Head Nurse Research Leadership Scale - Yuanli Guo; Keke Ma; Lina Guo; Xiaofang Dong; Caixia Yang; Min Wang; Huanhuan Gao; Peihua Lv (Wiley, 2023)
Abstract Aim To develop a Head Nurse Research Leadership Scale and evaluate its reliability and validity. Design A psychometric instrument validation study was conducted in two phases. Methods The item tool was generated based on a literature review, semi‐structured interview and brainstorming. Twenty experts validated the content of the initial version for two rounds. Thirty‐nine clinical nurses conducted the HNRLS‐v3 to test the readability of the items in pilot study I. Items were screened based on the critical ratio, correlation coefficient analysis, Cronbach's α coefficient and factor analysis using the data collected from 265 nurses in pilot study II. A cross‐sectional survey was conducted in six hospitals to evaluate the reliability and validity between 4 January 2022 and 15 January 2022. Three hundred and sixteen nurses participated in this survey, and 60 completed the questionnaire to validate the test-retest reliability between 1 February and 6 February. Results A 15‐item Head Nurse Research Leadership Scale based on 5 dimensions was developed, and the content validity was satisfied. The 15 items accounted for 77.9% of the variance. Confirmatory factor analysis showed acceptable convergent validity and discriminant validity. The Cronbach's α coefficient, split‐half reliability and test-retest reliability of the scale were 0.966, 0.9633 and 0.927, respectively.